A Sandwich Nanostructure of Gold Nanoparticle Coated Reduced Graphene Oxide for Photoacoustic Imaging-Guided Photothermal Therapy in the Second NIR Window - Wang, Zhihua; Sun, Xiao; Huang, Ting; Song, Jibin; Wang, Yudong (Frontiers in Bioengineering and Biotechnology, 2020)
We explore a sandwich-type gold nanoparticle coated reduced grapheme oxide (rGO-AuNP) as an effective nanotheranostic platform for the second near-infrared (NIR-II) window photoacoustic (PA) imaging-guided photothermal therapy (PTT) in ovarian cancer. The PEG was loaded onto the AuNPs surface to increase the stability of nanostructure. The forming rGO-AuNPs- PEG revealed very strong SERS signal, NIR-II PA signal and high photothermal efficiency against tumor upon 1061 nm laser irradiation. The prominent performance was attributed to the plasmonic coupling of AuNPs, and the enhanced response of rGO and the plasmonic AuNP. Thus, our study demonstrates that the rGO-AuNP nanocomposite could promise to be a potential photothermal agent and pave the way for the diagnosis and therapy of ovarian cancer in the future.